Carbon negative electrode material, preparation method thereof and lithium battery

CN117352725BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210753976.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-28
Publication Date
2026-10-30
Estimated Expiration
2042-06-28

AI Technical Summary

Technical Problem

[0008]本发明的目的是为了克服现有技术存在的碳负极材料在锂电池中的库伦效率低和循环稳定性差的问题,提供一种碳负极材料及其制备方法和锂电池,将本发明提供的碳负极材料应用于锂电池中,具有高比容量、高库伦效率和优异的充放电循环特性

Benefits of technology

[0016](1)本发明提供的碳负极材料具有一定的结晶度、碳层厚度和(002)晶面间距,将其应用于锂电池中,具有大的比容量、优异的库伦效率和良好的快速充电性能。从实施例可以看出,本发明的锂电池首圈库伦效率高于80%。在5C的恒流充放电倍率下,平均比容量大于500mAh·g-1,循环1000圈后的容量保持率高达97%。在50C的恒流充放电倍率下,平均比容量大于200mAh·g-1,循环1000圈后的容量保持率高达92%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117352725B_ABST
    Figure CN117352725B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium batteries, and discloses a carbon negative electrode material, a preparation method thereof and a lithium battery. The carbon negative electrode material is a layered material, the (002) crystal face interval of the carbon negative electrode material is 0.333-0.380 nm, the carbon layer thickness of the carbon negative electrode material is 2-5 nm, and the crystallinity of the carbon negative electrode material is 30-90. The preparation method of the carbon negative electrode material comprises the following steps: (1) reacting alkali metals, transition metal elements and carbon dioxide to obtain a reaction product; and (2) performing acid pickling, water washing and drying on the reaction product to obtain the carbon negative electrode material. The carbon negative electrode material provided by the application has high specific capacity, high coulomb efficiency and excellent charge-discharge cycle characteristics when applied to a lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, specifically to a carbon anode material, its preparation method, and a lithium battery. Background Technology

[0002] Since the commercialization of lithium-ion batteries, their negative electrodes have primarily used graphite or modified graphite. However, with the rapid development of the 3C industry, the tightening of petroleum energy, and the rapid development of renewable energy, higher demands have been placed on the energy density and performance of power sources. The theoretical specific capacity of graphite is only 372 mAh·g. -1 Furthermore, the actual capacity of graphite electrodes is already very close to this theoretical specific capacity. Therefore, developing new anode materials with high energy density, long cycle life, and safety and reliability has become a key research focus.

[0003] Graphene, another allotrope of carbon, is a thin-film hexagonal lattice structure. Graphene anode materials allow lithium ions to pass through 10-20 nm pores on their surface and be well stored between graphene sheets, enabling fast charging and optimal energy storage. Once in use, this type of battery is estimated to store 10 times more energy and charge faster than conventional graphite anodes. However, graphene's large specific surface area leads to the formation of a large SEI film during the initial charge-discharge cycle, increasing irreversible capacity and causing a decrease in coulombic efficiency. Furthermore, graphene as an anode material also suffers from the drawback of large potential changes accompanying the release and insertion of lithium ions within the material.

[0004] Besides graphite and graphene, carbon materials also have a wide range of structures and morphologies. Furthermore, the physical parameters of the material or the microstructure formed by the hexagonal crystal faces of carbon largely determine the electrochemical performance of the material. Therefore, regulating the morphology and structure of carbon materials is one of the effective methods for developing new power battery anode materials that meet the development requirements.

[0005] Currently, methods for preparing carbon materials include chemical vapor deposition (CVD) and high-temperature pyrolysis of organic carbon sources. CVD, in particular, can grow high-quality carbon material films by depositing carbon-containing organic matter onto a transition metal substrate. The morphology and structure of the prepared carbon material can be controlled by manipulating the morphology of the transition metal substrate. However, this method, based on the carbon deposition mechanism, requires sacrificing the transition metal substrate and has low production efficiency, making large-scale production of carbon materials difficult. On the other hand, the pyrolysis of solid carbon-containing organic matter results in low raw material utilization and generates VOCs and other waste gases during the production process, requiring tail gas treatment.

[0006] The paper "Potassium-chemical synthesis of 3D graphene from CO2 and its excellent performance in HTM-free perovskite solar cells" (Wei, W., Hu, B., Jin, F. et al. Journal of Materials Chemistry A, 2017, 5(17): 7749-7752.) discloses a method for preparing carbon materials using alkali metal reduction of carbon dioxide. In this method, the reaction of alkali metal with carbon dioxide generates carbon materials and corresponding carbonates in situ, which serve as templates to regulate the structure of the carbon materials. The carbon materials prepared using this method have a large specific surface area but poor crystallinity. However, these carbon materials exhibit low first-cycle coulombic efficiency and poor cycle stability in lithium-ion battery anodes.

[0007] Therefore, there is an urgent need to provide a carbon anode material with high coulombic efficiency, large specific capacity, and good cycle stability. Summary of the Invention

[0008] The purpose of this invention is to overcome the problems of low coulombic efficiency and poor cycle stability of carbon anode materials in lithium batteries in the prior art, and to provide a carbon anode material, its preparation method and lithium battery. When the carbon anode material provided by this invention is applied to lithium batteries, it has high specific capacity, high coulombic efficiency and excellent charge and discharge cycle characteristics.

[0009] To achieve the above objectives, the first aspect of the present invention provides a carbon anode material, wherein the carbon anode material is a layered material, the interplanar spacing of the carbon anode material (002) is 0.333-0.380 nm, the carbon layer thickness of the carbon anode material is 2-5 nm, and the crystallinity of the carbon anode material is 30-90, preferably 50-90.

[0010] A second aspect of the present invention provides a method for preparing a carbon anode material, the method comprising the following steps:

[0011] (1) React alkali metals, transition metals and carbon dioxide to obtain reaction products;

[0012] (2) The reaction product is acid washed, water washed and dried to obtain the carbon anode material.

[0013] A third aspect of the present invention provides a carbon anode material prepared by the method described in the second aspect above.

[0014] A fourth aspect of the present invention provides a lithium battery, the lithium battery comprising a positive electrode material containing lithium and a carbon negative electrode material as described in the first and third aspects above.

[0015] Through the above technical solution, the present invention can achieve the following beneficial effects:

[0016] (1) The carbon anode material provided by this invention has a certain degree of crystallinity, carbon layer thickness, and (002) interplanar spacing. When applied to lithium batteries, it exhibits high specific capacity, excellent coulombic efficiency, and good fast-charging performance. As can be seen from the examples, the first-cycle coulombic efficiency of the lithium battery of this invention is higher than 80%. At a constant current charge / discharge rate of 5C, the average specific capacity is greater than 500 mAh·g. -1 After 1000 cycles, the capacity retention rate is as high as 97%. At a constant current charge / discharge rate of 50C, the average specific capacity is greater than 200 mAh·g. -1 After 1000 cycles, the capacity retention rate is as high as 92%.

[0017] (2) The structural composition of the carbon anode material provided by the present invention can be controlled by reactants and reaction conditions during the preparation process, which is beneficial to the preparation of various types of carbon anode materials, to explore the influence of the structural properties of carbon anode materials on their performance, and to screen for more superior carbon anode materials.

[0018] (3) The carbon anode material provided by the present invention uses carbon dioxide as a carbon source for preparation, which is safer than using gaseous carbon-containing organic matter, and can realize the resource utilization of carbon dioxide, which is conducive to the realization of the dual carbon target. Attached Figure Description

[0019] Figure 1 It is a curve showing the change of carbon dioxide pressure over time during the preparation of carbon anode materials;

[0020] Figure 2 This is the XRD pattern of the carbon anode material;

[0021] Figure 3 This is the Raman spectrum of the carbon anode material;

[0022] Figure 4 This is an HRTEM image of the carbon anode material prepared in Example 1. Detailed Implementation

[0023] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0024] The first aspect of this invention provides a carbon anode material, wherein the carbon anode material is a layered material, the interplanar spacing of the carbon anode material (002) is 0.333-0.380 nm, preferably 0.335-0.350 nm, for example 0.335 nm, 0.340 nm, 0.345 nm, 0.350 nm, and any value within the range formed by any two of these values; the carbon layer thickness of the carbon anode material is 2-5 nm, preferably 2.5-4.5 nm, for example 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, and any value within the range formed by any two of these values; the crystallinity of the carbon anode material is 30-90, preferably 50-90, more preferably 55-85; for example 55, 60, 65, 70, 75, 80, 85, and any value within the range formed by any two of these values.

[0025] In a preferred embodiment of the present invention, the interplanar spacing of the carbon anode material (002) is determined by X-ray wide-angle diffraction (XRD), and the carbon layer thickness of the carbon anode material is calculated by the Scherrer formula based on the half-peak width of the (002) crystal plane of the XRD diffraction peak.

[0026] In a preferred embodiment of the present invention, the crystallinity (X) of the carbon anode material c ) is obtained by fitting the peaks of the XRD diffraction of the carbon anode material, and then using the amorphous bulge of the ungraphitized carbon material (I) c The peak area of ​​the diffraction peaks of the graphitized (002) crystal plane (I) n The value of K is calculated using the following formula, where K is 1.

[0027] X c =I c / (I c +KI n )×100%

[0028] In a preferred embodiment of the present invention, the lattice fringes of the carbon anode material can be observed using a high-magnification transmission electron microscope (HRTEM), indicating that the carbon anode material has good crystallinity.

[0029] In this invention, it can be seen from the XRD spectrum of the carbon anode material that the carbon layer of the carbon anode material is composed of a graphite structure.

[0030] Preferably, the carbon layer thickness of the carbon anode material indicates that each carbon layer of the carbon anode material contains an average of 5-15 layers of graphene, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15.

[0031] The carbon anode material provided by this invention possesses specific crystallinity, layer thickness, and interplanar spacing, effectively reducing irreversible capacity loss during the first charge-discharge cycle and improving the first-cycle coulombic efficiency. Furthermore, it helps to mitigate the large potential changes caused by lithium-ion insertion and release while increasing material capacity. Therefore, coin-type lithium batteries assembled based on this carbon anode material exhibit high specific capacity, excellent coulombic efficiency, and good fast-charging performance.

[0032] In a preferred embodiment of the present invention, in the Raman spectrum of the carbon anode material, the ratio of the peak height of the 2D peak to the peak height of the G peak is 0.2-0.7, preferably 0.3-0.6, for example, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, and any value within the range formed by any two of these values; the full width at half maximum (FWHM) of the D peak is 50-100 cm. -1 The preferred size is 60-90cm. -1 For example, 60cm -1 65cm -1 70cm -1 75cm -1 80cm -1 85cm -1 90cm -1 And any value within the range formed by any two of these values; the full width at half maximum (FWHM) of the G peak is 50-100 cm. -1 The preferred size is 70-90cm. -1 More preferably 70-80cm -1 For example, 70cm -1 72cm -1 74cm -1 76cm -1 78cm -1 80cm -1 And any value within the range formed by any two of these values; the peak spacing between the D and G peaks is 180-250 cm. -1 The preferred size is 230-250cm. -1 For example, 230cm -1 235cm -1 240cm -1 245cm -1 250cm -1 And any value within the range formed by any two of these values.

[0033] Compared with the Raman spectra of carbon materials prepared without the addition of transition metal elements in the prior art, the Raman spectra of the carbon anode material provided by the present invention show a larger ratio of the peak height of the 2D peak to the peak height of the G peak, indicating that the prepared carbon material is composed of multilayer graphene; the full width at half maximum (FWHM) of the D peak is smaller, indicating that the material has a single type of defect; the peak spacing between the D peak and the G peak is smaller, indicating that there are fewer material defects. Therefore, the Raman spectrum further shows that the carbon anode material provided by the present invention has better crystallinity and a larger layer thickness.

[0034] In a preferred embodiment of the present invention, the specific surface area of ​​the carbon anode material is 200-900 m². 2 g -1 For example, 200m 2 g -1 300m 2 g -1 400m 2 g -1 500m 2 g -1 600m 2 g -1 700m 2 g -1 800m 2 g -1 900m 2 g -1 And any value within the range formed by any two of these values; the average pore size of the carbon anode material is 2-6 nm, preferably 2.5-5.5 nm, for example, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, and any value within the range formed by any two of these values; the electrical conductivity of the carbon anode material is 4.5-10 S·cm. -1 Preferably, it is 5-9.5 S·cm -1 For example, 5S·cm -1 5.5S·cm -1 6S·cm -1 6.5S·cm -1 7S·cm -1 7.5S·cm -1 8S·cm -1 8.5S·cm -1 9S·cm -1 9.5S·cm -1 And any value within the range formed by any two of these values.

[0035] In this invention, the specific surface area and pore size of the carbon anode material are determined by N2 adsorption / desorption curves; the conductivity of the carbon anode material is measured by the four-probe method.

[0036] The inventors of this invention discovered in their research that the specific surface area, average pore size, and conductivity of the carbon anode material are related to the type of alkali metal used in the preparation process. For the same alkali metal, compared to carbon materials prepared without the addition of transition metal elements in existing technologies, the carbon anode material provided by this invention exhibits a significantly reduced specific surface area, increased average pore size, and increased conductivity, thus demonstrating high specific capacity, high coulombic efficiency, and excellent charge-discharge cycle characteristics in lithium batteries.

[0037] A second aspect of the present invention provides a method for preparing a carbon anode material, the method comprising the following steps:

[0038] (1) React alkali metals, transition metals and carbon dioxide to obtain reaction products;

[0039] (2) The reaction product is acid washed, water washed and dried to obtain the carbon anode material.

[0040] The inventors of this invention discovered that by using alkali metals to reduce carbon dioxide to prepare carbon materials, and by adding transition metal elements during the reaction process, a carbon anode material completely different from that prepared without the addition of transition metal elements can be produced. Specifically, the alkali metal reacts with carbon dioxide to generate carbon materials and corresponding carbonates. The carbonates act as template agents to regulate the structure of the carbon materials. The added transition metal elements significantly increase the reaction rate of the redox reaction process, resulting in better crystallinity of the prepared carbon anode material and significantly improving its first-cycle coulombic efficiency and cycle stability.

[0041] The present invention does not particularly limit the manner in which the reaction described in step (1) is carried out, as long as it enables the alkali metal, transition metal element and carbon dioxide to react in contact. Preferably, the reaction described in step (1) includes: mixing the alkali metal and transition metal element, placing them in a reactor, and then introducing carbon dioxide into the reactor.

[0042] The present invention does not particularly limit the reactor, and the reaction can be carried out in various reactors conventionally used in the art, such as a tubular furnace.

[0043] In a preferred embodiment of the present invention, the alkali metal is selected from at least one of lithium, sodium and potassium, and can be an alkali metal element lithium, sodium or potassium, or a mixture or alloy formed by any two or three of the alkali metal elements, preferably an alloy formed by sodium and potassium, lithium or sodium.

[0044] In a preferred embodiment of the present invention, the mass ratio of sodium to potassium in the sodium-potassium alloy is 1-3:2-4. By changing the mass ratio of sodium to potassium, the specific surface area of ​​the carbon anode material can be adjusted, thereby affecting the first-cycle coulombic efficiency and specific capacity of the lithium battery.

[0045] The present invention does not particularly limit the type of transition metal, as long as it can accelerate the redox reaction rate. Preferably, the transition metal is selected from at least one of iron, copper, nickel, and silver.

[0046] The inventors of this invention discovered in their research that by controlling the mass ratio of alkali metal to transition metal elements, the morphology of the prepared carbon anode material can be controlled. Specifically, the specific surface area, average pore size, and conductivity of the prepared carbon anode material can be controlled, thereby affecting the performance of the lithium battery.

[0047] In a preferred embodiment of the present invention, in order to obtain a carbon anode material with high specific capacity, high coulombic efficiency and good cycle stability, the mass ratio of the alkali metal to the transition metal is 1:0.05-0.5, preferably 1:0.1-0.3.

[0048] In a preferred embodiment of the present invention, in order to ensure that the added alkali metal is completely reacted, the molar amount of carbon dioxide introduced into the reactor should be more than three times the molar amount of the added alkali metal; preferably, the molar ratio of carbon dioxide to alkali metal is 3-20:1, and more preferably 5-15:1.

[0049] In a preferred embodiment of the present invention, in order to promote the full reaction of alkali metal, transition metal element and carbon dioxide, the reaction conditions include: a reaction temperature of 200-800℃, preferably 300-600℃; and a reaction time of 10min-10h, preferably 10min-6h.

[0050] In this invention, the reaction temperature is increased from room temperature to the above-mentioned reaction temperature at a heating rate of 5-10℃ / min; the reaction time is the time from the start of timing when the reaction temperature is reached to the end of the reaction.

[0051] In a preferred embodiment of the present invention, the acid washing, water washing and drying process in step (2) includes: washing the reaction product with acid, filtering and recovering the filter cake, repeatedly washing and filtering with water, and then drying the solid product obtained after filtration.

[0052] The present invention does not have any particular limitation on the method of acid washing in step (2), as long as it can remove the carbonate impurities and transition metals generated in the reaction. Preferably, the acid washing is performed by immersing the reaction product in acid for 5-24 hours.

[0053] In a preferred embodiment of the present invention, the amount of acid used should exceed three times the total molar amount of the alkali metal and the added transition metal element.

[0054] In a preferred embodiment of the present invention, the acid is selected from hydrochloric acid and / or nitric acid.

[0055] The present invention does not impose a particular limitation on the concentration of the acid, as long as the amount of acid used meets the above conditions. Preferably, the mass concentration of the hydrochloric acid is 10-37 wt%, and the mass concentration of the nitric acid is 20-65 wt%.

[0056] The present invention does not have any particular limitation on the method of water washing in step (2), as long as the pH value of the filtrate after water washing is 6.5-7.5.

[0057] In a preferred embodiment of the present invention, the drying conditions include a temperature of 80-120°C and a time of 8-15 hours.

[0058] In a preferred embodiment of the invention, the drying can be carried out in conventional drying equipment in the art, such as a blower drying oven.

[0059] A third aspect of this invention provides a carbon anode material prepared by the method described in the second aspect above. The properties of the carbon anode material have been described in detail in the first aspect and will not be repeated here.

[0060] A fourth aspect of this invention provides a lithium battery comprising a positive electrode material containing lithium and the carbon negative electrode material described in the first and third aspects. The lithium battery provided by this invention exhibits high specific capacity, excellent coulombic efficiency, and good fast-charging performance.

[0061] The structure of the lithium battery provided by this invention is well known to those skilled in the art, and is not limited herein. This invention does not particularly limit the specific composition of the lithium-containing cathode material; it can be any existing lithium-containing cathode material used in the art.

[0062] The present invention will be described in detail below through embodiments. In the following embodiments and comparative examples,

[0063] The XRD pattern of the carbon anode material was measured using an XRD-6100 X-ray diffractometer. The (002) interplanar spacing, crystallinity, and carbon layer thickness of the carbon anode material were obtained by analyzing the XRD pattern. Specifically, the (002) interplanar spacing of the carbon anode material was calculated using Bragg's formula; the carbon layer thickness was obtained by calculating the half-maximum width (WHM) of the (002) crystal planes in the XRD diffraction using Scherrer's formula; and the crystallinity (X...) of the carbon anode material was determined by... c) is determined by XRD diffraction peak fitting, using the amorphous bulge (I) of ungraphitized carbon material. c The peak area of ​​the diffraction peaks of the graphitized (002) crystal plane (I) n The value of K is calculated using the following formula, where K is 1.

[0064] X c =I c / (I c +KI n )×100%

[0065] The Raman spectra of carbon anode materials were measured using an inVia Qontor Raman spectrometer.

[0066] The morphology of the carbon anode material was characterized using a Talos F200X G2 transmission electron microscope.

[0067] Unless otherwise stated, all raw materials used in the following examples and comparative examples are commercially available products.

[0068] Example 1

[0069] Sodium and potassium metal blocks were removed separately from the kerosene. The kerosene on the metal surfaces was wiped clean, and the oxide layer was removed with a knife. 1g of sodium and 4g of potassium were weighed and placed in a beaker. After a period of time, the sodium and potassium dissolved to form a sodium-potassium alloy containing 20wt% sodium. The prepared sodium-potassium alloy was placed in a corundum boat, 1g of nickel powder was added, and the mixture was stirred thoroughly. The mixture was then transferred to a tube furnace, ensuring that the molar amount of carbon dioxide introduced was 10 times the molar amount of the added sodium-potassium alloy. For the reactor used in this experiment, carbon dioxide was introduced at 350 kPa. The temperature was increased to 450℃ at a rate of 5℃ / min, and the reaction was carried out at this temperature for 6 hours. After the reaction was complete, the furnace temperature was allowed to cool naturally to room temperature, and the reaction product was removed.

[0070] The reaction product prepared above was placed in a beaker, and 100 mL of concentrated hydrochloric acid with a mass concentration of 37 wt% was added. After soaking for 12 h, it was rinsed with a large amount of deionized water until the pH of the filtrate was 7. Then, the solid product obtained after filtration was dried in a forced-air drying oven at 80 °C for 12 h to obtain a carbon anode material, denoted as carbon material 1.

[0071] Pressure changes over time during the reaction process, such as Figure 1 As shown.

[0072] The XRD pattern of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 2 As shown. Calculations show that the prepared carbon anode material (002) has a crystal plane spacing of 0.349 nm, a carbon layer thickness of 2.80 nm, and a crystallinity of 61.

[0073] The Raman spectrum of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 3 As shown. From Figure 3 As can be seen, the ratio of the peak height of peak 2D to that of peak G is 0.6, and the half-width at half-maximum of peak D is 67 cm. -1 The half-width of peak G is 77cm. -1 The peak spacing between peaks D and G is 235 cm. -1 .

[0074] This invention uses the carbon anode material prepared in Example 1 as an example for transmission electron microscopy (TEM) testing, such as... Figure 4 As shown. Figure 4 The HRTEM image of the prepared carbon anode material is shown from... Figure 4 The carbon anode material exhibits distinct lattice fringes, indicating that it possesses good crystallinity.

[0075] Example 2

[0076] Carbon anode material was prepared according to the method of Example 1, except that 0.5 g of nickel powder was added. The resulting sample was designated as carbon material 2. The pressure change over time during the reaction is as follows: Figure 1 As shown.

[0077] Example 3

[0078] Carbon anode material was prepared according to the method in Example 1, except that 0.3 g of nickel powder was added. The resulting sample was designated as carbon material 3. The pressure change over time during the reaction is as follows: Figure 1 As shown.

[0079] Example 4

[0080] Weigh 5g of sodium into a corundum boat, add 2g of nickel powder, mix thoroughly, and then transfer to a tube furnace. Ensure that the molar amount of carbon dioxide introduced is 10 times the molar amount of sodium added. For the reactor used in this experiment, introduce carbon dioxide at 350kPa. Increase the temperature to 550℃ at a heating rate of 5℃ / min, and react at this temperature for 30min. After the reaction is complete, allow the furnace temperature to cool naturally to room temperature, and then remove the reaction product.

[0081] The reaction product prepared above was placed in a beaker, and 100 mL of concentrated hydrochloric acid with a mass concentration of 37 wt% was added. After soaking for 12 h, it was rinsed with a large amount of deionized water until the pH of the filtrate was 7. Then, the solid product obtained after filtration was dried in a forced-air drying oven at 80 °C for 12 h to obtain the carbon anode material, denoted as carbon material 4.

[0082] Example 5

[0083] The carbon anode material was prepared according to the method of Example 1, except that "concentrated hydrochloric acid with a mass concentration of 37 wt%" was replaced with "concentrated nitric acid with a mass concentration of 65 wt%", and the resulting sample was designated as carbon material 5.

[0084] The XRD pattern of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 2 As shown. Calculations show that the prepared carbon anode material (002) has a crystal plane spacing of 0.347 nm, a carbon layer thickness of 2.81 nm, and a crystallinity of 59.

[0085] The Raman spectrum of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 3 As shown. From Figure 3 As can be seen, the ratio of the peak height of peak 2D to that of peak G is 0.55, and the half-width of peak D is 64 cm. -1 The half-peak width of peak G is 75cm. -1 The peak spacing between peaks D and G is 244 cm. -1 .

[0086] Example 6

[0087] Weigh 0.5g of lithium into a corundum boat, add 0.1g of nickel powder, mix thoroughly, and then transfer to a tube furnace. Ensure that the molar amount of carbon dioxide introduced is 5.84 times the molar amount of lithium added. For the reactor used in this experiment, introduce carbon dioxide at 100kPa. Increase the temperature to 450℃ at a heating rate of 5℃ / min, and react at this temperature for 1 hour. After the reaction is complete, allow the furnace temperature to cool naturally to room temperature, and then remove the reaction product.

[0088] The reaction product prepared above was placed in a beaker, and 100 mL of concentrated hydrochloric acid with a mass concentration of 37 wt% was added. After soaking for 12 h, it was rinsed with a large amount of deionized water until the pH of the filtrate was 7. Then, the solid product obtained after filtration was dried in a forced-air drying oven at 80 °C for 12 h to obtain a carbon anode material, denoted as carbon material 6.

[0089] The XRD pattern of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 2 As shown. Calculations show that the prepared carbon anode material (002) has a crystal plane spacing of 0.337 nm, a carbon layer thickness of 4.044 nm, and a crystallinity of 81.

[0090] The Raman spectrum of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 3 As shown. From Figure 3 As can be seen, the ratio of the peak height of peak 2D to that of peak G is 0.36, and the half-width at half-maximum of peak D is 90 cm. -1 The half-width of peak G is 76 cm. -1 The peak spacing between peaks D and G is 248 cm. -1 .

[0091] Example 7

[0092] The carbon anode material was prepared according to the method of Example 1, except that 2g of sodium and 3g of potassium were weighed and placed in a beaker. After a period of time, the sodium and potassium dissolved to form a sodium-potassium alloy containing 40wt% sodium. The reaction time was 30min. The sample obtained was denoted as carbon material 7.

[0093] Example 8

[0094] The carbon anode material was prepared according to the method of Example 1, except that 3g of sodium and 2g of potassium were weighed and placed in a beaker. After a period of time, the sodium and potassium dissolved to form a sodium-potassium alloy containing 60wt% sodium. The reaction time was 30min. The sample obtained was denoted as carbon material 8.

[0095] Example 9

[0096] Carbon anode material was prepared according to the method in Example 1, except that "nickel powder" was replaced with "iron powder" and the reaction time was 30 min. The resulting sample was designated as carbon material 9.

[0097] Example 10

[0098] Carbon anode material was prepared according to the method in Example 1, except that "nickel powder" was replaced with "copper powder" and the reaction time was 30 min. The resulting sample was denoted as carbon material 10.

[0099] Example 11

[0100] The carbon anode material was prepared according to the method of Example 1, except that the temperature was increased to 700°C at a heating rate of 5°C / min. The resulting sample was designated as carbon material 11.

[0101] Example 12

[0102] The carbon anode material was prepared according to the method of Example 1, except that the temperature was increased to 350°C at a heating rate of 5°C / min, and the reaction was carried out at this temperature for 8 hours. The resulting sample was designated as carbon material 12.

[0103] Example 13

[0104] Carbon anode material was prepared according to the method of Example 1, except that the amount of nickel powder added was 2.5g, and the resulting sample was designated as carbon material 13.

[0105] Comparative Example 1

[0106] Carbon anode materials were prepared according to the method in Example 1, except that nickel powder was not added during the preparation process. The resulting sample was designated as Control Sample 1.

[0107] Pressure changes over time during the reaction process, such as Figure 1 As shown. From Figure 1 It can be seen that, compared with the case without the addition of transition metal elements, the carbon dioxide pressure decreases very rapidly when transition metal elements are added during the preparation of carbon anode materials, indicating that the added transition metal elements can accelerate the reaction rate.

[0108] The XRD pattern of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 2 As shown. Calculations show that the prepared carbon anode material (002) has a crystal plane spacing of 0.377 nm, a carbon layer thickness of 1.52 nm, and a crystallinity of 9.

[0109] The Raman spectrum of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 3 As shown. From Figure 3 As can be seen, the ratio of the peak height of peak 2D to that of peak G is 0.17, and the half-width at half-maximum of peak D is 230 cm. -1 The half-width of peak G is 95cm. -1 The peak spacing between peaks D and G is 260 cm. -1 .

[0110] Comparative Example 2

[0111] Carbon anode materials were prepared according to the method in Example 4, except that nickel powder was not added during the preparation process, and the reaction time was 6 hours. The resulting sample was designated as control sample 2.

[0112] Comparative Example 3

[0113] Carbon anode materials were prepared according to the method in Example 6, except that nickel powder was not added during the preparation process, and the reaction time was 6 hours. The resulting sample was designated as control sample 3.

[0114] The XRD pattern of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 2 As shown. Calculations show that the prepared carbon anode material (002) has a crystal plane spacing of 0.355 nm, a carbon layer thickness of 2.1 nm, and a crystallinity of 27.

[0115] The Raman spectrum of the prepared carbon anode material was measured, and the measurement results are as follows: Figure 3 As shown. From Figure 3 As can be seen, the ratio of the peak height of peak 2D to that of peak G is 0.22, and the half-width of peak D is 157 cm. -1 The half-peak width of peak G is 65cm. -1 The peak spacing between peaks D and G is 256 cm. -1 .

[0116] Test case

[0117] In the following test examples, the specific surface area and pore size of the carbon anode material were determined by N2 adsorption / desorption curves; the conductivity of the carbon anode material was measured by the four-probe method.

[0118] (1) Performance testing of carbon anode materials

[0119] The specific surface area, average pore size, and conductivity of the carbon anode materials prepared in Examples 1-13 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.

[0120] Table 1

[0121] Carbon materials 1 520.4 4.1 8.34 Carbon materials 2 563.8 3.8 7.89 Carbon materials 3 867.3 2.9 5.43 Carbon materials 4 387.3 4.1 8.1 Carbon materials 5 393.2 4 7.53 Carbon materials 6 213.5 5.4 9.36 Carbon materials 7 430.2 4.3 8.79 Carbon materials 8 321.8 4.5 8.65 Carbon materials 9 490.3 4 8.53 Carbon materials 10 513.9 4.1 8.92 Carbon materials 11 639.2 4.5 6.70 Carbon materials 12 480.1 3.8 8.43 Carbon materials 13 515.7 4.1 8.25 Comparison Sample 1 1103.5 2.6 4.02 Comparison Sample 2 605.2 3.6 3.87 Comparison Sample 3 390.6 3.8 4.98

[0122] The performance test results (Table 1) of the carbon anode materials prepared in Examples 1 and 1, 4 and 2, and 6 and 3 show that, compared with those without transition metals, the carbon anode materials prepared with the addition of transition metals have smaller specific surface areas, larger average pore sizes, and higher conductivity. This indicates that the morphology of the carbon anode materials can be controlled by the transition metals added during the preparation process.

[0123] (2) Assembly and performance testing of lithium batteries

[0124] Electrolyte: 1 mol / L LiPF6 solution of ethyl carbonate, methyl ethyl carbonate and dimethyl carbonate (volume ratio 1:1:1).

[0125] Preparation of carbon anode material: The carbon anode material, conductive carbon black and PVDF are mixed in a mass ratio of 8:2:1 and uniformly coated on 11μm copper foil using a coater. Then, the mixture is vacuum dried at 80℃ for 10h and cut into 12mm diameter round pieces using a cutting machine for later use.

[0126] Button cell assembly: In the glove box, stack the negative electrode shell, spring, gasket, lithium sheet, separator, carbon negative electrode material sheet, and positive electrode shell in sequence. Add 50μL of electrolyte before and after placing the separator. Finally, place the stacked 2032 button cell on a pressure sealing machine for sealing. Let the assembled button cell stand overnight for later use.

[0127] Battery testing: Battery performance was tested using constant current charge-discharge. All batteries were cycled 3-5 times at 0.1C, and then subjected to charge-discharge cycle tests at 5C and 50C rates respectively. The test results are shown in Table 2.

[0128] Table 2

[0129]

[0130]

[0131] As can be seen from the results in Table 2, the lithium battery made with the carbon anode material provided by this invention exhibits significantly better performance than the comparative example. The lithium battery of this invention achieves a first-cycle coulombic efficiency exceeding 80%. At a constant current charge-discharge rate of 5C, the average specific capacity is greater than 500 mAh·g. -1 After 1000 cycles, the capacity retention rate is above 80%, reaching as high as 97%. At a constant current charge / discharge rate of 50C, the average specific capacity is greater than 200 mAh·g. -1 After 1000 cycles, the capacity retention rate is over 75%, reaching as high as 92%.

[0132] In summary, the carbon anode material provided by this invention has a certain degree of crystallinity and layer thickness, and the lithium battery made from it has a large specific capacity, excellent coulombic efficiency, and good fast charging performance.

[0133] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A carbon anode material, characterized in that, The carbon anode material is a layered material, with a (002) interplanar spacing of 0.333-0.380 nm, a carbon layer thickness of 2-5 nm, a crystallinity of 50-90, and a specific surface area of ​​200-900 m². 2 g -1 The average pore size of the carbon anode material is 2-6 nm; each carbon layer of the carbon anode material contains an average of 5-15 layers of graphene.

2. The carbon anode material according to claim 1, wherein, The conductivity of the carbon anode material is 4.5-10 S·cm. -1 .

3. The carbon anode material according to claim 1, wherein, In the Raman spectrum of the carbon anode material, the ratio of the peak height of the 2D peak to the peak height of the G peak is 0.2-0.7; the full width at half maximum (FWHM) of the D peak is 50-100 cm⁻¹. -1 The half-width of peak G is 50-100 cm. -1 The peak spacing between peaks D and G is 180-250 cm. -1 .

4. The carbon anode material according to claim 3, wherein, The ratio of the peak height of 2D to that of G is 0.3-0.6; the half-width at half-maximum (FWHM) of the D peak is 60-90 cm. -1 The half-width of peak G is 70-90 cm. -1 The peak spacing between peaks D and G is 230-250 cm. -1 .

5. A method for preparing the carbon anode material according to any one of claims 1 to 4, characterized in that, The method includes the following steps: (1) React alkali metals, transition metals and carbon dioxide to obtain reaction products; (2) The reaction product is acid-washed, water-washed, and dried to obtain the carbon anode material; Wherein, the transition metal is selected from at least one of iron, copper, nickel and silver; the acid used for pickling is selected from hydrochloric acid and / or nitric acid; The molar ratio of carbon dioxide to alkali metal is 5-15:1; And / or, the reaction temperature is 300-600℃; And / or, the reaction time is 10 min to 6 h.

6. The method according to claim 5, wherein, The alkali metal is selected from at least one of lithium, sodium, and potassium.

7. The method according to claim 5 or 6, wherein, The mass ratio of the alkali metal to the transition metal is 1:0.05-0.

5.

8. The method according to claim 7, wherein, The mass ratio of the alkali metal to the transition metal is 1:0.1-0.

3.

9. A lithium battery, characterized in that, The lithium battery includes a positive electrode material containing lithium and a carbon negative electrode material as described in any one of claims 1-4.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode active material, lithium ion battery negative electrode, lithium ion battery, battery pack and battery power vehicle

    CN109553080A

  • Application of carbon material with high hydrogen evolution overpotential in lead / carbon battery

    CN111740174A